Effects of Olympic Combat Sports on Older Adults’ Health Status: A Systematic Review - Herrera-Valenzuela, T; Aedo-Munoz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The aim of this systematic review was to analyse the studies centered on the effects of Olympic combat sports (OCS [i.e., boxing, fencing, judo, karate, taekwondo, wrestling]) on older adults’ physical-functional, physiological, and psychoemotional health status. The review com-prised randomised-controlled trials with OCS interventions, including older adults (>60 years), and measures of physical-functional, physiological, and/or psychoemotional health. The studies were searched through SCOPUS, PubMed/MEDLINE, Web of Science, PsycINFO, and EBSCO databases until 5 January 2021. The PRISMA-P and TESTEX scales were used to assess the quality of the selected studies. The protocol was registered in PROSPERO (code: CRD42020204034). Twelve OCS intervention studies were found (scored ≥60% for methodological quality), comprising 392 females and 343 males (mean age: 69.6 years), participating in boxing, judo, karate, and taekwondo. The qualitative analysis revealed that compared to controls, OCS training improved muscle strength, cardiorespiratory capacity, agility, balance, movement, attention, memory, mental health, anxiety, and stress tolerance. Meta-analysis was available only for the chair stand test, and an improvement was noted after OCS training compared to control. In conclusion, OCS interventions improves older adults’ physical-functional, physiological, and psychoemotional health. Our systematic review con-firms that OCS training has high adherence (greater than 80%) in older adults. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.